Epidemiological profile of people aged 50 years and over with HIV/AIDS in Roraima, Brazil (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile of people aged 50 years or older living with the human immunodeficiency virus, in Roraima, Brazil. Methodology: This is a descriptive, cross-sectional, population-based observational study, using secondary data from individuals aged 50 years or older with HIV/AIDS in Roraima notified in Sinan, from 2010 to 2019. Results: 342 cases of HIV/AIDS were reported in in this age group in Roraima (10.4% of the total of 3277 cases registered among all population groups). The cases occurred mainly in brown-skinned individuals, with low education, whose most frequent occupations were housewife, retiree/pensioner, prospector and agricultural worker. The main route of exposure to HIV was heterosexual. The age group with the highest incidence was 50 to 59 years old (72.8%), with a predominance of males (64.6%). Regarding the staging of the syndrome, 199 (58.2%) of the individuals evaluated had manifest AIDS at the time of notification of the case. As for the country of origin, a significant increase was observed in the number of notifications in patients from Venezuela (p